Cultivation Strategies of Kenaf (Hibiscus cannabinus L.) as a Future Approach in Malaysian Agriculture Industry - Diwiyaa A. G. Vayabari; Zul Ilham; Norsharina Md Saad; Siti Rokhiyah Ahmad Usuldin; Danial’ Aizat Norhisham; Muhamad Hafiz Abd Rahim; Wan Abd Al Qadr Imad Wan-Mohtar (Horticulturae, 2023)
In recent years, kenaf has gained significant global attention as a more cost-effective, adaptable, and manageable alternative to other fibre crops. India and China, with nearly 70% of the global kenaf production, have emerged as the leading producers of kenaf plants. While kenaf was traditionally valued for its paper production, it has evolved into a multipurpose crop with diverse industrial applications over the past two decades. Conventional soil-based cultivation methods for kenaf require up to six months for plant maturity. However, in vitro propagation techniques offer a promising alternative that enables faster growth and reduced labour costs. In vitro propagation can be achieved using solid and liquid media, with limited research available on the pure liquid culture method for kenaf. This review aims to introduce and compare the production of kenaf using solid and liquid media, with a specific focus on the emerging country of Malaysia, which seeks to harness the potential of kenaf cultivation for the 15th Sustainable Development Goal, “life on land”, and its contribution to the economy.